Legal Risks for the Victims of the Criminal Act of Murder Plan on a Recovery Plan through Restitution (Open Society Conference, 2023)
One form of compensation for victims of criminal acts is restitution. Restitution in accordance with the Principle of Restoration in its Original Condition (restutio in integrum) is an effort that the victim of a crime must be returned to its original condition before the crime occurred even though it is based on the fact that it is impossible for the victim to return to his original condition. A crime can cause harm to another person, namely the victim of a crime. To obtain compensation, a victim of a crime can take the procedure provided by the Criminal Procedure Code, namely the merger of cases for compensation. After the enactment of Law Number 13 of 2006 concerning Protection of Witnesses and Victims, all victims of criminal acts were also given the option to apply for compensation in the form of restitution through the LPSK. However, it turns out that there are several problems that arise in the implementation of mechanisms to obtain restitution for victims of these crimes. These problems are not only about the rules, but also about the institutions that are authorized to assist victims of criminal acts in obtaining their right to restitution.